(untitled) (Academicia Globe: Inderscience Research, 2022)
The study included the manufacture of the chicken burger product by adding various fatty tissues that included of sheep fat tail tissues, calf hump and camel hump, as well as belly fat for sheep, calf and camels at a rate of 10% for each treatment, burgers pieces were formed with a weight of (50) grams, thickness of (7) mm and diameter of (11) cm. The burger pieces stored in plastic containers under frozen storage conditions at -18 C and for a period 45 days. Physicochemical and qualitative changes were studied during that period. The chicken burger indicated pH (7.9). ) Added to the sheep fat tail tissues to reach (5.4) after frozen storage -18 Celsius for 45 days. The chicken burger also indicated a percentage of bound water that reached (71.24) % added to the fat of the sheep fat tail tissues , to decrease to (66.9)% after 45 days of frozen storage. While the percentage of free fatty acids in chicken burgers (0.12 – 0.41) % in the burger added to it camel hump and sheep fat tail tissues respectively, the percentage of tri glycerides in chicken burger ranged between (104 – 372) mg / dL. While the cholesterol content in the chicken burger ranged (30.8 -77.4) mg/dL in the burger with belly fat added. The amount of the iodin number (4.06 –35.53) % in the chicken burger. The peroxide number (20-40)% ranged in the chicken burger. The melting point of chicken burger fat also ranged from 38 to 45 degrees Celsius. The sensory evaluation of the chicken burger received a sensory rating (8.3– 9) for the color trait, (8.3 –9) for the flavor trait, (7.3 – 8.3 ) for the juiciness trait, ( 8.1– 9) for the aroma trait and (7.3– 8.0) for the trait of general acceptance.